2020
DOI: 10.7556/jaoa.2020.040
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Research Interests and Perceptions of First-Year Medical Students at 4 Colleges of Osteopathic Medicine

Abstract: Context There are limited data regarding the experiences of and attitudes toward research participation among osteopathic medical students despite rapidly increasing enrollment and expansion of the number of osteopathic medical schools. Objective To assess first-year osteopathic medical students’ experience with research, their interest in it, their perceptions of its value, and barriers to participation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Additionally, all OMSs can benefit from learning those research skills (e.g., literature review, hypothesis generation) that have applications to clinical practice, and research experiences improve OMSs’ resumes for residencies [ 15 ]. However, a survey study of OMS-I students at four COMs suggests that not all OMSs (177/328 [54.0%]) are interested in research [ 16 ], and medical students have been shown to report greater satisfaction with voluntary, compared to mandatory, research programs [ 17 ]. Further, requiring disinterested OMSs to conduct research under faculty mentorship is a drain on financial resources and faculty members’ time [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, all OMSs can benefit from learning those research skills (e.g., literature review, hypothesis generation) that have applications to clinical practice, and research experiences improve OMSs’ resumes for residencies [ 15 ]. However, a survey study of OMS-I students at four COMs suggests that not all OMSs (177/328 [54.0%]) are interested in research [ 16 ], and medical students have been shown to report greater satisfaction with voluntary, compared to mandatory, research programs [ 17 ]. Further, requiring disinterested OMSs to conduct research under faculty mentorship is a drain on financial resources and faculty members’ time [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most SRPs provided some or all OMSs with stipends, and some programs offered course credit. Although a survey of OMS-I students at four COMs showed both monetary compensation (213/328 [64.9%]) and extra credit in courses (195/328 [59.5%]) to be strong incentives for OMSs to participate in research, the same study also showed that a slim majority of respondents were either currently doing research or planning to do research while in medical school [ 16 ]. In the present study, seven SRPs provided neither incentive, including the three SRPs with the highest proportions of participating students relative to total enrollment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For our main survey, we used a descriptive survey study design to investigate the previous research experiences and current perceptions of research among first-year osteopathic medical students at Marian University College of Osteopathic Medicine (MU-COM) in Indianapolis, Indiana. The main survey instrument (Supplemental File S1), which was used in our prior publication [10], consisted of fifteen items: fourteen multiple-choice questions, with select questions allowing for participants to write in responses, and one question asking participants to input their age. Osteopathic medical students in the classes of 2022, 2023, 2024, and 2025 who had entered medical school three weeks earlier, were sent an email inviting them to voluntarily participate in an anonymous survey on research interests.…”
Section: Main Surveymentioning
confidence: 99%
“…), only 59% of osteopathic medical students do so [9]. This is notable because research by us and others indicates that the majority of osteopathic medical students express interest in clinical research [10][11][12][13]. Thus, it is important to identify osteopathic medical students' motivations for participating in research as well as the real and/or perceived barriers preventing participation in research during osteopathic medical school.…”
Section: Introductionmentioning
confidence: 99%